Measuring the Accounting Profession's Ethical Sensitivity: The Influence of Money Attitudes - Wulandari, Devi; Rahmiati, Alfa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The purpose of this research is to examine the attitude of the accounting profession (public accountants) towards money and their ethical perceptions and to determine whether the ethical perception of the accounting profession can be influenced by the attitude of the accounting profession towards money. This research uses a survey approach, where the questionnaire is conducted based on the Money Ethical Scale (MES). MES was subjected to exploratory factor analysis to test its dimensions and through cluster analysis, respondents were classified based on similarities in attitudes towards money. The relationship between attitudes toward money and ethical perceptions was confirmed using a Multivariate Analysis of Variance (MANOVA) test. The results show that respondents are generally ethically oriented and that women are more ethical than men. Differences exist in terms of respondents' attitudes towards money and the MANOVA results show that money attitudes are good predictors of ethical perceptions of the accounting profession. The findings of this research suggest that understanding individuals' attitudes toward money may be an important way of predicting how they will behave when faced with ethical dilemmas. The analysis makes an important contribution to the previous literature by highlighting the influence of money attitudes on ethical perceptions.